2021
DOI: 10.1002/ehf2.13217
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of CHADS2, R2CHADS2, and CHA2DS2‐VASc scores for predicting incident atrial fibrillation in heart failure with preserved ejection fraction patients

Abstract: Aims Coexisting of atrial fibrillation (AF) in patients with heart failure with preserved ejection fraction (HFpEF) could increase the risk of mortality. In this study, we aimed to assess the values of the CHADS2, R2CHADS2, and CHA2DS2-VASc scores for AF prediction in HFpEF patients. Methods and results We performed a retrospective analysis on symptomatic HFpEF patients in the TOPCAT (Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist) trial. Associations of the CHADS2, R2CHAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…3 Additionally, AF and other cardiovascular diseases share common risk factors, which are part of the components of the CHA 2 DS 2 -VASc score. Thus, several studies explored the predictive value of the CHA2DS2–VASc score in patients with cardiovascular diseases such as heart failure, 4,5 acute coronary syndrome 6 (ACS), valvular heart disease 7 (VHD) and thromboembolic events 8 (TE). However, the prognostic value of this score in CCU patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…3 Additionally, AF and other cardiovascular diseases share common risk factors, which are part of the components of the CHA 2 DS 2 -VASc score. Thus, several studies explored the predictive value of the CHA2DS2–VASc score in patients with cardiovascular diseases such as heart failure, 4,5 acute coronary syndrome 6 (ACS), valvular heart disease 7 (VHD) and thromboembolic events 8 (TE). However, the prognostic value of this score in CCU patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This rate is higher than that observed in the TOPCAT trial, also in patients with HFpEF, that reported an incidence rate of 1.8 per 100 patient-years over a median follow-up of 3.3 years. 12 Empagliflozin did not lower the risk of new-onset atrial fibrillation. Similar findings have been reported in patients with HFrEF, in whom dapagliflozin did not reduce the risk of incident atrial fibrillation in patients in sinus rhythm at baseline.…”
Section: Discussionmentioning
confidence: 97%
“…We previously showed that CHA 2 DS 2 ‐VASc (C statistic, 0.62) scores did not achieve an excellent predictive ability for stroke, regardless of AF status. 9 , 20 Abdul‐Rahim and coworkers developed a complicated model for stroke in patients with HFpEF without AF, with a higher performance from the CHARM‐Preserved (C statistic, 0.71) and I‐Preserve (C statistic, 0.73) trials; furthermore, the model worked exceptionally well with an external validation cohort of TOPCAT (C statistic, 0.73). 4 These results suggested the generality of risk scores across different baseline characteristics across the population.…”
Section: Discussionmentioning
confidence: 99%
“…The calculation of these risk scores has been described previously. 20 The C index of a BNP‐added risk‐predicting model versus existing risk‐predicting model was compared by using the method of Delong et al 21 The continuous net reclassification improvement (NRI) index and integrated discrimination improvement (IDI) index examined the improvement. CIs of C index, NRI scores, and IDI scores were computed by bootstrap resampling.…”
Section: Methodsmentioning
confidence: 99%